2020
DOI: 10.1155/2020/5097109
|View full text |Cite
|
Sign up to set email alerts
|

Synergism and Antagonism of Two Distinct, but Confused, Nrf1 Factors in Integral Regulation of the Nuclear-to-Mitochondrial Respiratory and Antioxidant Transcription Networks

Abstract: There is hitherto no literature available for explaining two distinct, but confused, Nrf1 transcription factors, because they shared the same abbreviations from nuclear factor erythroid 2-related factor 1 (also called Nfe2l1) and nuclear respiratory factor (originally designated α-Pal). Thus, we have here identified that Nfe2l1Nrf1 and α-PalNRF1 exert synergistic and antagonistic roles in integrative regulation of the nuclear-to-mitochondrial respiratory and antioxidant transcription profiles. In mouse embryon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In our study, we found that H 2 O 2 -induced oxidative stress inhibited proliferation, migration and invasion of U251 cells and promoted cell apoptosis, which was consistent with the results of Dalavaikodihalli et al (2019). NRF1, a redox-sensitive transcription factor, is vital for maintaining healthy redox homeostasis (Yuan et al, 2018;Zhang et al, 2020). Deletion of NRF1 function leads to a sharp increase in ROS and oxidative damage (Hu et al, 2022).…”
Section: Knockdown Of Nor1 Could Alleviate the Antioxidative Stress E...supporting
confidence: 84%
“…In our study, we found that H 2 O 2 -induced oxidative stress inhibited proliferation, migration and invasion of U251 cells and promoted cell apoptosis, which was consistent with the results of Dalavaikodihalli et al (2019). NRF1, a redox-sensitive transcription factor, is vital for maintaining healthy redox homeostasis (Yuan et al, 2018;Zhang et al, 2020). Deletion of NRF1 function leads to a sharp increase in ROS and oxidative damage (Hu et al, 2022).…”
Section: Knockdown Of Nor1 Could Alleviate the Antioxidative Stress E...supporting
confidence: 84%
“…To gain an insight into the underlying mechanism for mitochondrial dysfunction caused by loss of Nrf1α –∕– , we here examined the constitutive expression of two nuclear respiratory factors αPal NRF1 and GABPα NRF2 [ 38 , 39 ], cofactor PGC1α, and critical target genes (responsible for mitochondrial DNA replication and transcription, ETC/OXPHOS gene expression, and mitochondrial biogenesis [ 40 ]). The results showed that basal mRNA expression levels of αPal NRF1 , GABPα NRF2 and co-targeting mitochondrial transcription factors TFAM (transcription factor A, mitochondrial), TFB1M (transcription factor B1, mitochondrial) and TFB2M (transcription factor B2, mitochondrial), together with PGC1α , but not PGC1ß , were down-regulated, though to different extents, in Nrf1α –∕– cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…No reuse allowed without permission. (14,23), protein homeostasis (proteostasis) (12,24), redox balance and signaling control (25,26). It is of crucial significance to note that the experimental cell model of Nrf1α -/with pathophysiological phenotypes appears to largely resemble those manifested by the liver-specific Nrf1 knockout mice.…”
Section: Discussionmentioning
confidence: 99%